Litigation in the management of urinary stone disease. (1st May 2022) - Yang, Bingyuan; Goldsmith, Louise; Turney, Ben; Reynard, John
Abstract : Objective: To present common technical and non‐technical issues leading to medicolegal litigation, illustrated by a series of 54 cases, with the aim of using these examples to prevent harm to patients and to prevent surgeons from having to experience the stress of litigation. Methods: A series of 78 medicolegal litigation cases reviewed by a single expert witness over 13 years from 2008 to 2021 was analysed by two reviewers. Twenty‐nine cases were identified as having a non‐technical learning point and 25 were identified as having a technical learning point. These are discussed using illustrative examples and the steps that could have avoided these issues are considered. Results: All major issues and themes are illustrated with cases demonstrating the errors that lead to litigation and the often‐simple steps that can be taken to avoid them. Out of 29 non‐technical issues, 13 involved consent issues (45%), eight involved delays in treatment (28%) and eight involved failure to provide adequate safeguarding advice (28%). Out of 25 technical issues, 13 cases involved intra‐operative problems (52%) including nine ureteric injuries, eight involved errors or omissions in the immediate preoperative period (32%) and four resulted from decisions around emergency decompression of the obstructed infected kidney. These emergency cases featured complications of amputation (two out of four) and death (one out of four). These decisions are complex and there are many subtleties to these cases, which are discussed in detail. Conclusion: We hope that this case series highlights the potentially catastrophic outcomes of even small errors of judgement, and allows careful stone surgeons to learn from the experiences of those unfortunate others without having to encounter these situations themselves.